Bone Healing and Inflammation: Principles of Fracture and Repair - ElHawary, Hassan; Baradaran, Aslan; Abi-Rafeh, Jad; Vorstenbosch, Joshua; Xu, Liqin; Efanov, Johnny Ionut (Seminars in Plastic Surgery, 2021)
Bones comprise a significant percentage of human weight and have important physiologic and structural roles. Bone remodeling occurs when healthy bone is renewed to maintain bone strength and maintain calcium and phosphate homeostasis. It proceeds through four phases: (1) cell activation, (2) resorption, (3) reversal, and (4) bone formation. Bone healing, on the other hand, involves rebuilding bone following a fracture. There are two main types of bone healing, primary and secondary. Inflammation plays an integral role in both bone remodeling and healing. Therefore, a tightly regulated inflammatory response helps achieve these two processes, and levels of inflammation can have detrimental effects on bone healing. Other factors that significantly affect bone healing are inadequate blood supply, biomechanical instability, immunosuppression, and smoking. By understanding the different mechanisms of bone healing and the factors that affect them, we may have a better understanding of the underlying principles of bony fixation and thereby improve patient care.
Keywords: bone healing; fracture repair; bone inflammation; osteomyelitis